2019
DOI: 10.1177/0256090919861010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Marketing and Well-being: A Review of Selective Databases

Abstract: This article presents a systematic review of social marketing and well-being. It summarizes key findings of different research articles and identifies important research gaps that need to be addressed by future research. This study explores, analyses, and presents a literature review by closely examining 94 articles. The articles focusing on social marketing and well-being have been retrieved from the databases of leading social marketing and management journals for the period 1998-2017. Adopting a content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
0
15
0
1
Order By: Relevance
“…A new approach is how to carry out a marketing strategy using spiritual elements in society (Vasconcelos, 2011). The concept of marketing with a spiritual practice has a meaning related to religion and is accompanied by spiritual values such as openness, honesty, humility, and trustworthiness and is built with noble actions (Bhat et al, 2019;Othman et al, 2018). Open, containing meaning, and the company does not hide things that consumers should indeed know.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…A new approach is how to carry out a marketing strategy using spiritual elements in society (Vasconcelos, 2011). The concept of marketing with a spiritual practice has a meaning related to religion and is accompanied by spiritual values such as openness, honesty, humility, and trustworthiness and is built with noble actions (Bhat et al, 2019;Othman et al, 2018). Open, containing meaning, and the company does not hide things that consumers should indeed know.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…There are six universal components of the social marketing model, which include: (1) equity, (2) social networks as determinants of behaviour, (3) critical marketing, (4) sustainability, (5) scaling, and (6) comprehensive programming or the total market approach (TMA).…”
Section: Discussionmentioning
confidence: 99%
“…If the principles of commercial marketing are to be followed, the first task of social marketing would be to focus on the consumer in order to understand what are their wants and needs as well as to persuade the consumer to buy what is being offered. For the last years social marketing has been widely studied not only by foreign but also by Lithuanian researchers (Akbar et al, 2021;Bastos et al, 2021;Bhat et al, 2019;Johns, 2020;Kennedy, 2016;Truong et al, 2019;Jokubauskas, 2003). In other words, social marketing has become an important factor in attracting customers.…”
Section: Introductionmentioning
confidence: 99%
“…A positive link between social marketing and well-being is evident. For example, social marketing is an important tool in reducing alcohol consumption, tobacco consumption as well as preventing sexual harassment and thereby increasing the well-being of individuals [13,32]. Also, in connection with socialmarketing and well-being, recent research [33] has demonstrated that a marketing approach to moderate consumption is regarded "as an opportunity to increase individuals' wellbeing through avoiding over-indebtedness" [18].…”
Section: Transformation From Growth-oriented System To Sustainable Wementioning
confidence: 99%